Предмет:
МатематикаАвтор:
аноним(tga - ctga) (1 + cosa) (1 - cosa) = = (tga - ctga) (1 - cos^2(a))= = (sina/cosa - cosa / sina) · (1 - cos^2(a)) = = ((sin^2(a) - cos^2(a)) / (sina · cosa)) · sin^2(a) = = ( - cos(2a) · sin^2(a)) / (sina · cosa) = = - cos(2a) · tga;Ответ: - cos(2a) · tga;
Автор:
brandtshlgДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть